Risk Sharing in the Presence of a Public Good - Josef Schroth (Bank of Canada, 2015)
This paper studies an economy where agents can spend resources on consuming a private good and on funding a public good. There is asymmetric information regarding agents' relative preference for private versus public good consumption. I show how private good consumption should be coordinated across agents within each period to ensure efficient contributions to fund the public good. If agents contributed similar amounts in the past, then coordination takes the form of positively correlated contributions in the current period. If an agent contributed more in the past, then coordination prescribes statecontingent socially wasteful private good consumption in the current period for that agent.
Keywords: E62; H21; H23; H77; D82; D86; 330; Fiscal policy; Financial stability; Financial system regulation and policies